Analysis of the Level of Welfare and Factors Influencing the Welfare of the Community Around the Durian Luncuk I Nature Reserve Area and Durian Luncuk II Nature Reserve Area, Jambi Province - Salsabila Hapsari, Qanita; Fazriyas, Fazriyas; Marwoto, Marwoto (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Communities around the Durian Luncuk I and II Nature Reserves in Jambi Province are highly dependent on forest resources, but still face welfare problems such as low income, education, and basic facilities. Purpose: This study aims to analyze the level of welfare, identify factors that influence welfare, and formulate strategies to improve the welfare of communities around nature reserve areas. Method: The method used is a quantitative approach through a questionnaire survey of 111 respondents and multiple linear regression analysis, as well as a qualitative approach through a SWOT analysis of 21 key informants and supporters. Results and Discussion: The level of community welfare varies from moderate to low. The factors that most influence welfare are household income, land area, number of productive workers, and education level. The proposed strategy includes strengthening community capacity and synergy with related agencies. Conclusion: The welfare of communities around nature reserves still needs to be improved through strategies that take into account local socio-economic conditions, so that they are in line with environmental conservation goals.